Innovating Videography Instruction in Vocational Schools: A DBR-Based Multimedia Approach - Dita Luthfillah; Asrul Huda; Ika Parma Dewi; Yevgeniya Daineko (Sagamedia Teknologi Nusantara, 2025)
This study aims to develop and validate an interactive learning medium for the Vocational Videography course at SMK Negeri 2 Padang Panjang using a Design-Based Research (DBR) approach. The media, developed with Adobe Captivate, integrates multimedia elements such as visuals, audio, video tutorials, and interactive quizzes to enhance student engagement and comprehension. The development process followed iterative DBR phases, including problem analysis, prototype design, expert validation, implementation, and reflection. Validation by six experts in educational technology and subject matter resulted in ratings of